Evaluation of techniques for the detection of Karnal bunt (Neovossia indica) of wheat (Triticum aestivum) - VARSHNEY, J L (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1996-98 to compare the merits of different techniques for the detection of Karnalbunt of wheat (Triticum aestivum L. emend. Fiori & Paol.). Karnal bunt of wheat caused by Neovossia indica (Mitra)Mundkur is a high risk disease of national and international importance. The infection can be examined by visualinspection of dry seeds, washing test and seed soak method. Visual inspection of dry seeds and seed soak method helpto estimate the number of infected seeds in a seed lot. However, in view of the nature, establishment and spread of thedisease, detection of even a single teliospore of the pathogen carried in any form is significant. Seed soak method isuneconomical, time-consuming, cumbersome, unreliable and quantitatively inaccurate because many of the teliosporesare lost during decantation and drying. Nevertheless, at times the number of infected seeds decrease because many ofthe most severely infected seeds get fragmented and subsequently lost during decantation. However, teliospores arereliably detected by washing test which is easy, rapid, less time consuming and quantitatively accurate and, therefore,it has been adopted by several countries.